O papel das estratégias de comunicação no processo de aquisição de português como língua estrangeira: um estudo com alunos intercambistas da UFG - Faria, Pedro Henrique Andrade de (2015)
This study aims at investigating and understanding how communicative strategies (CS) are present in Portuguese as a Foreign Language (PFL) classroom and how they contribute to the promotion of interaction between learner-learner and learner-teacher. The study also seeks to identify communicative strategies which are present in the PFL lessons, understand which strategies contribute to the promotion of interaction and negotiation of meanings in class and understand, as well, apprentices’ perception of communication in the classroom and the use of CS in class. Sixteen exchange students of a PFL class at UFG and the teacher of that class participated in this case study during the first semester of 2014. The principles of qualitative research were used to collect and analyze the data. The theoretical perspective basis of this study was proposed by Tarone (1980). Regarding the CS, we also used the sociocultural theory of Vigotski (2007, 2009) to discuss issues related to the interaction in the classroom. Finally, we discuss FL/L2 intercultural education, proposed by Corbett (2003), Kachuru (2008) and Risager (2005, 2006, 2010). Based on the theoretical assumptions, we show, by analyzing the data, the CS present in the PFL classes and how these CS contribute to the interaction of learners and the exchange of meaning. Finally, we demonstrate learners’ conception of learning a FL/L2 and how this conception reflects their attitude in the classroom. We believe that, from the understanding of the importance of the CS and a FL teaching approach, which takes into account intercultural aspects, we can develop a FL learning environment where learners feel comfortable in communicating regardless of the linguistic problems found during the communicative process.